Histopathology of vasculitis - G. Bajocchi; A. Cavazza (PAGEPress Publications, 2018)
The range of pathologies that are related to primitive vasculitis is broad, complex and not as typical as we would expect. Clinicians should be aware that several forms of primitive and systemic vasculitis, regardless of the size of the affected vessel, may exhibit identical histological alterations. This observation has important clinical implications as it means that cases of vasculitis do not correspond clinically and histologically. Thus, while histology remains the diagnostic gold standard, it can be used only as part of the most complete clinical assessment possible. Another point worth of the clinician's attention is that vasculitis histology changes over time, as do disease evolution and activity, even without considering the masking effects of treatment and the possibility of sampling error due to the patchy occurrence of vasculitis. The purpose of this review is to identify the most common forms of vasculitis in clinical practice, and to provide guidance to the clinician on the pathology of the vessels.